Strategy Combining Mammalian Fats with Supplementation of Pungent Spices in Aquafeeds, to Mitigate Negative Impacts of Fish Oil Replacement in Fish Performance, Fillet Quality and Hepatic Condition of Gilthead Seabream (Sparus Aurata) - Reyes-Lopez, F; Vallejos-Vidal, E (Elsevier B.V., 2024)
The replacement of fish oil (FO) in aquafeeds usually leads to imbalances in the dietary content of n-3 and n-6 polyunsaturated fatty acids (PUFA), with negative consequences for fish performance, health, and fillet quality. Animal-rendered fats are an alternative lipid source high in saturated fatty acids, potentially sparing n-3 PUFA from oxidation, and with lower n-6 PUFA contents than plant-based oils, especially in the case of mammalian fats (MF). Hence, this work assessed the effect of replacing 45% FO by MF (negative control, NC) compared to a diet containing only FO (positive control, PC) in gilthead seabream (Sparus aurata, initial body weight: 85 ± 4 g, mean ± standard deviation) at low water temperature. In addition, we studied the effect of supplementing the NC diet with a combination of pungent spices with hypolipidemic and anti-inflammatory properties at three inclusion levels: 0.05 (SPICY0.05%), 0.1 (SPICY0.1%), and 0.15% (SPICY0.15%). At the end of the trial (112 days), FO substitution by MF led to poorer fish performance in terms of body weight (BW), specific growth rate (SGR), feed conversion ratio (FCR), and protein efficiency ratio (PER). Supplementation of the NC diet with spices numerically improved SGR, FCR and PER at all inclusion levels (non-significantly different from the PC group), being FCR and PER significantly different from the NC group in the SPICY0.1% and SPICY0.15% treatments. A remarkable increase in lipid level was observed in fillets of fish fed the NC diet, but was fully counteracted by spice supplementation, especially in fish fed the SPICY0.15% diet. A lower fat accumulation was also found in the liver of fish fed the SPICY0.1% and SPICY0.15% diets, with respect to the PC and NC groups. The fillets fatty acid profile mostly reflected the diet composition, but the SPICY0.15% diet modified it in an inverse direction to that observed in the NC, to more closely resemble the profile of fish fed the PC diet. In particular, the SPICY0.15% diet reduced fillet levels of MUFA, linoleic and linolenic acids, and increased n-3 LC-PUFA (including EPA and DHA), compared to the NC. A microarray-based transcriptomic analysis revealed a better hepatic health status, as indicated by different biological processes associated to immunity. Overall, supplementation with the combination of pungent spices at 0.15% enabled the incorporation of alternative lipid sources, such as MF, in aquafeeds without significantly compromising growth and feeding performance, liver health, and quality of the edible product. © 2024 Elsevier B.V.